2020
DOI: 10.1088/1367-2630/ab8ab2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting turbulence small-scale behavior using velocity gradient triple decomposition

Abstract: Turbulence small-scale behavior has been commonly investigated in literature by decomposing the velocity-gradient tensor (Aij) into the symmetric strain-rate (Sij) and anti-symmetric rotationrate (Wij) tensors. To develop further insight, we revisit some of the key studies using a triple decomposition of the velocity-gradient tensor. The additive triple decomposition formally segregates the contributions of normal-strain-rate (Nij), pure-shear (Hij) and rigid-body-rotation-rate (Rij). The decomposition not onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 43 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…However, while the q A -r A plane efficiently characterizes local streamline geometries at critical points, additional parameters are required to fully describe all geometries (Das & Girimaji 2020a). Following Das & Girimaji (2020b), we consider the local streamline geometry in the context of the modes of deformation of a fluid parcel: extensional straining, (symmetric and antisymmetric) shearing and rigid rotation. The well-known Cauchy-Stokes decomposition of the VGT, Ã = S + W , disambiguates contributions from the symmetric strain rate tensor, S = ( Ã + ÃT )/2, and the antisymmetric vorticity tensor, W = ( Ã − ÃT )/2.…”
Section: Velocity Gradients and Vorticesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, while the q A -r A plane efficiently characterizes local streamline geometries at critical points, additional parameters are required to fully describe all geometries (Das & Girimaji 2020a). Following Das & Girimaji (2020b), we consider the local streamline geometry in the context of the modes of deformation of a fluid parcel: extensional straining, (symmetric and antisymmetric) shearing and rigid rotation. The well-known Cauchy-Stokes decomposition of the VGT, Ã = S + W , disambiguates contributions from the symmetric strain rate tensor, S = ( Ã + ÃT )/2, and the antisymmetric vorticity tensor, W = ( Ã − ÃT )/2.…”
Section: Velocity Gradients and Vorticesmentioning
confidence: 99%
“…For example, the original triple decomposition (Kolář 2007) has been used to show that lifetimes of fundamental flow structures at macroscopic scales (where viscosity can be neglected) can be related to stability of rigid rotation, linear instability of pure shearing and exponential instability of irrotational straining (Hoffman 2021). At small scales, the more recent triple decomposition has been used to show that pure shearing is typically the dominant contributor to energy dissipation (Wu et al 2020) and intermittency (Das & Girimaji 2020b) in turbulent flows. Further, the symmetric and antisymmetric components of γ * are given by γ * S = ( γ * + γ * T )/2 and γ * W = ( γ * − γ * T )/2, respectively.…”
Section: Velocity Gradients and Vorticesmentioning
confidence: 99%
See 2 more Smart Citations
“…To distinguish between rigid rotation and pure shearing in total vorticity, the residual vorticity was proposed by Kolář (2007), and the precise mathematical expression of the rigid vorticity ω R was given by Liu et al (2018Liu et al ( , 2019, which is referred to as Liutex (originally known as Rortex). Moreover, according to the studies of Das and Girimaji (2020b), it is found that low-pressure regions are strongly associated with rigid rotation motions, while pure shearing is associated with nearly zero pressure fluctuations. Vortex-induced pressure fluctuation and vibration are important topics in system stability studies of hydroenergy machinery.…”
Section: Introductionmentioning
confidence: 97%